USE OF THE CONCESSION MECHANISM FOR THE DEVELOPMENT OF DIFFICULT FOR ACCESS DEPOSITS OF MINERAL RESOURCES - Z. M. Nazarova; Y. A. Leonidova (Известия высших учебных заведений: Геология и разведка, 2017)
The problems of the concession development are considered, which is one of the forms of public-private partnership during developing difficult for access mineral deposits. Data on the historical experience of this form of management in the world and in Russia, including in mineral resources use, are given. The specifics of the implementation of the concession mechanism in the mineral resources use in Russia are reflected, as well as the factors that impede the development of the concession mechanism in modern conditions in the mining sectors of the Russian Federation. The necessity of using concessions for the creation of industrial infrastructure, which is necessary for the development of difficult for access mineral deposits is substantiated.